Enzymatic hydrolysis of cassava stems for butanol production of isolated Clostridium sp. - B. Saekhow; S. Chookamlang; A. Na-u-dom; N. Leksawasdi; V. Sanguanchaipaiwong (Energy Reports, 2020)
This research focused on the hydrolysis of cassava stems (CS) and subsequent utilization as a carbon source for the cultivation of isolated Clostridium sp. To yield the highest amount of reducing sugars (RS), the studies on the pretreatment with sodium hydroxide (NaOH) and the hydrolysis with cellulases, amylases, and mixed enzymes were carried out. Afterwards, the hydrolysate was utilized for the cultivation of isolated Clostridium sp. Experimental results revealed that CS after 1.0 M NaOH pretreatment at 121~°C for 15 min and cellulase hydrolysis (Accellerase® 1500, 2500 CMC U/g CS) obtained 10.94~±~0.29 g/L RS concentration. Hydrolysis of CS with amylases (Termamyl® 120, 1.2 U/g CS and AMG 300L™ 3.5 U/g CS) provided 34.85~±~0.75 g/L RS and the maximum RS amount of 47.90~±~0.39 g/L was obtained from the hydrolysis with mixed enzymes (Termamyl® 120, 1.2 U/g CS, AMG 300L™ 3.5 U/g CS followed by Accellerase® 1500, 2500 CMC U/g CS). From the cultivation of Clostridium sp. G10 using CS hydrolysate, the highest dry cell weight concentration of 1.28~±~0.07 g/L was obtained with 11.68~±~0.31 g/L butanol. It could be concluded that CS hydrolysate was comparable with glucose for utilization as a carbon source for butanol production.
Keywords: 330; Acetone-butanol-ethanol fermentation; Anaerobe; Cassava stem; Clostridium sp.